O jeito de ser livreiro no Brasil: notas sobre o mercado de bens simbólicos - Silva, Sergio Eduardo Sampaio [UNIFESP] (2019)
This work is a conscious effort to put a light on the collective sentiment between the booksellers, that becomes evident in the way they act, feel and think between their peers. Historically and sociologically, the concept of habitus, investigated from the group's own memory, presents itself as an analytical tool to describe and reflect on the social configurations of the book market in each period of its history. Researching in the long term, about two hundred years of existence, it is possible to analyze the changes and the permanence of the general characteristics of the behavior of printer-editor-booksellers in Brazil. The present study shows that, over time, professionals have been (re) producing their own ways of making economic and symbolic exchanges between authors, intermediaries, and readers, directly interfering with the book's supply and demand. During the history of the way of being a bookseller, it is observed that, at first, a single person added several functions, both in practice (printing and selling), as well as symbolically (writing and editing). Over time, book professionals remained interdependent from the point of view of production and distribution but separated into three distinct sub-behaviors: printers associated themselves with the industrialists; editors with intellectuals; and the booksellers with merchants.